2019
DOI: 10.3844/ajassp.2019.101.112
|View full text |Cite
|
Sign up to set email alerts
|

Application of ZnO Nano Rods for the Batch Adsorption of Cr(VI): A Study of Kinetics and Isotherms

Abstract: The present study reports the synthesis of nano Zinc Oxide (ZnO) and its adsorption behaviour. The ZnO obtained by precipitation method were found to be well-defined nano rods arranged like flower. The shape, size and structure of ZnO were characterized from X-Ray Diffraction (XRD), Energy Dispersive X-ray (EDX) and Scanning Electron Microscope (SEM) analysis. These nano rods were utilized for the adsorption of hexavalent chromium ions [Cr(VI)] from their aqueous solution by using batch adsorption technique. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…This corresponds to the hexagonal wurtzite phase (JCPDS 36-1541). The XRD pattern also shows intense and sharp diffraction peaks at 2⊔ values of 20 101), ( 110), (012), ( 111), ( 200), (021), ( 112), ( 202), ( 103), (211), ( 212) and (301), respectively. This matched well to crystalline SiO 2 nanoparticles with JCP2_83-0539 of the ⊍-quartz phase of silica.…”
Section: Ftir Spectroscopymentioning
confidence: 98%
See 1 more Smart Citation
“…This corresponds to the hexagonal wurtzite phase (JCPDS 36-1541). The XRD pattern also shows intense and sharp diffraction peaks at 2⊔ values of 20 101), ( 110), (012), ( 111), ( 200), (021), ( 112), ( 202), ( 103), (211), ( 212) and (301), respectively. This matched well to crystalline SiO 2 nanoparticles with JCP2_83-0539 of the ⊍-quartz phase of silica.…”
Section: Ftir Spectroscopymentioning
confidence: 98%
“…The removal values for Hg(II), Pb(II), Bi(III) and Cd(II) reported were 86.8%, 97.1%, 61.2% and 80.9%, respectively. Kamath et al 20 successfully synthesized ZnO nanorods for Cr(VI) removal. Those authors reported 0.00165 mg g −1 to be the highest adsorption capacity.…”
Section: Introductionmentioning
confidence: 99%
“…; the demand for zinc oxide is always rising [28,29]. In addition, zinc oxide nanoparticles have been investigated for water treatment by adsorption various heavy metal such as Cu(II), Cr(VI), Cd(II) and Pb(II) [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Angelin et al (2015) [16] employed spherical ZnO-NPs (8 nm), manufactured by the sol-gel technique, as an adsorbent for Hg(II), Cd(II), Bi(III), and Pb(II) elimination under the reaction parameters of duration (60 min), temperature (30 • C), dosage (0.250 g), and [M n+ ] (0.01 mol L −1 ) The reported elimination values for Cd(II), Pb(II), Bi(III), and Hg(II), were 61.2%, 97.1%, 80.9%, and 86.8%, respectively. Kamath et al (2019) [17] produced a ZnO nanosphere to effectively remove Cr 6+ , and the authors reported that the q e was 0.00165 mgg −1 . In contrast, the instability of zinc oxide nanoparticles in an aqueous matrix is a disadvantage.…”
Section: Introductionmentioning
confidence: 99%